Onion Peel Powder as an Antioxidant-Rich Material for Sausages Prepared from Mechanically Separated Fish Meat - Jan Bedrníček; Jaromír Kadlec; Ivana Laknerová; Jan Mráz; Eva Samková; Eva Petrášková; Lucie Hasoňová; František Vácha; Vladimír Kron; Pavel Smetana (MDPI AG, 2020)
Mechanically separated fish meat (MSFM) can be used for the manufacturing of ready-to-eat products, such as sausages; however, it is highly perishable. Several plant by-products, including onion peel, which is rich in polyphenol antioxidants, can be added to food to extend shelf life. This study investigated the effects of the addition of onion peel powder (OPP) to sausage made from MSFM. Sausages were divided into four groups with different amounts of added OPP: 0% (control), 1%, 2%, and 3%. Cooked sausages were stored for 28 days at 5 °C. Samples were analyzed for thiobarbituric acid reactive substances, antioxidant activity, total polyphenol content, pH, and organoleptic properties. The addition of OPP significantly increased antioxidant activity and total polyphenol content and decreased pH, indicating acidic nature of OPP. Polyphenols from OPP effectively suppressed lipid oxidation. A 1-2% addition of OPP enhanced sensory properties. After the 28-day storage, the control samples received the lowest sensory score, due to the presence of a strong fishy odor, which was not present in samples with OPP. HPLC-MS/MS analysis revealed that quercetin is the most dominant compound in OPP. Overall, the results indicate that the addition of OPP in amounts of 1-2% can extend shelf life, without the deterioration of sensory properties.